Bahasa Asli Kitab Perjanjian Baru - Bakhoh Jatmiko (SANCTUM DOMINE: JURNAL TEOLOGI, 2015)
Some modern scholars have brought vital discussion related to the origin language of the New Testament. Instead of being written in Greek, some of them believed that, not just partially or some words, but the whole New Testament manuscripts was originally written in Aramaic language. They are known as Aramaic Primacist. Besides historical and some other external evidences, linguistic approach also can be used to discover in what language the New Testament Manuscript originally written.